2020
DOI: 10.1007/s13243-020-00090-y
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating design for remanufacturing in the early design stage: a design management perspective

Abstract: Adopting design approaches that allow products to last multiple use-cycles supports European Commission objectives to reduce greenhouse gas emissions and reduce primary material impacts. Remanufacturing is an example of an appropriate circular strategy and it can be applied in a variety of industries that are intensive materials users. However, most companies have not yet adopted design strategies facilitating remanufacturing at scale. In this paper, we explored how design management can facilitate the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The system can feedback the optimized key design parameters for remanufacturing to the product's initial design. We conduct manufacturability assessments of improved designs [6]. We form a feedback design model through repeated optimization and finally obtain a product design solution with good manufacturability.…”
Section: Figure 1 Negotiating Paths Of Offensive and Defensive Ideali...mentioning
confidence: 99%
“…The system can feedback the optimized key design parameters for remanufacturing to the product's initial design. We conduct manufacturability assessments of improved designs [6]. We form a feedback design model through repeated optimization and finally obtain a product design solution with good manufacturability.…”
Section: Figure 1 Negotiating Paths Of Offensive and Defensive Ideali...mentioning
confidence: 99%
“…Product design is another critical issue for the success of remanufacturing reverse logistics (Govindan et al, 2016b). Boorsma et al (2021) identified both opportunities and barriers for implementing design for remanufacturing in OEMs, and Lindkvist Haziri and Sundin (2020) proposed a remanufacturing-to-OME information framework to allow a collaborative and better design management in the initial stage. Using both vector space model and case-based reasoning, Ke et al (2020) developed an intelligent decision-support framework to help OMEs with the implementation of design for remanufacturing.…”
Section: 21) Strategic Decision-support Modelsmentioning
confidence: 99%
“…Yet, the implementation of, for example, design guidelines, often finds significant resistance in design teams, as optimising costs, time-to-market, and functionality for the first use-cycle are prioritized [7][8][9][10]. Understanding the benefits and value of strategic, early-stage, design for remanufacturing is key and can help improve the level of sustainable production [11][12][13]. The need for early-stage design integration is also acknowledged in the field of eco-design, which remanufacturing can be considered part of [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, design management is a field of study that is concerned with developing and integrating design, and bringing awareness to its strategic potential [31,32]. In a previous paper, an initial set of design management roles for remanufacturing was defined based on literature and interviews with companies [11]. Key roles were 'connecting different disciplines within the company to develop relevant, high-quality offers', 'making technology roadmaps at an early design stage', and 'identifying the intangible value of remanufacturing to a company'.…”
Section: Introductionmentioning
confidence: 99%